Tracheal Stenosis in Neuro Myelitis Optica Spectrum Disorders: Airway Management in the ICU - Nugraha, Taufiqo; Sugiarto, Adhrie (Jurnal Komplikasi Anestesi, 2026)
Background: A woman, 32 years old, with Neuro Myelitis Optica Spectrum Disorder (NMOSD) came to the emergency department complaining dyspnea, productive cough, wheezing and low oxygen levels. She was intubated using an uncuff endotracheal tube (ETT) size. 5. Subsequently, an inadvertent dislodgement of the ETT in the intensive care unit (ICU). A Thoracic CT imaging showed tracheal narrowing at the thoracic 1-2 level, approximetely 58% of the lumen width. A Multidisciplinary case conference was convened to plan balloon dilatation bronchoscopy with a bedside tracheostomy as a backup crash airway protocolCase: NMOSD attacks can be life-threatening, leading to respiratory failure requiring orotracheal intubation (OTI). Patient with a history of prolonged and repeated intubation in the ICU may develop post-intubation tracheal stenosis (PITS). Discussion: The patient experienced ETT dislodgement, prompting reintubation with ETT cuffs number 4 and 6 using a video laryngoscope and an adult bougie. Reintubation with a larger ETT size was is necessitated by reduced mucosal edema following adequate steroid, inhalation, and antibiotic therapy. Balloon dilatation bronchoscopy of mucosal stenosis via LMA was successfully performed, followed by intubation using ETT cuff no. 8 with guided bronchoscopy. The patient was successfully weaned from mechanical ventilation with a leak test before extubation.Conclusion: Airway management by considering the location and degree of stenosis as well as the patient's general condition. Balloon dilatation with bronchoscopy offers good results in patients with tracheal stenosis who are not eligible for surgery.